Perioperative complications and short-term outcomes of abdominal sacrocolpopexy, laparoscopic sacrocolpopexy, and laparoscopic pectopexy for apical prolapse - Biler,Alper (2018)
ABSTRACT Objective: To investigate differences in perioperative complications and short-term outcomes of patients who underwent abdominal sacrocolpopexy / sacrohysteropexy, laparoscopic sacrocolpopexy / sacrohysteropexy, or laparoscopic pectopexy due to apical prolapse. Materials and Methods: A retrospective cohort study was performed on 110 patients who underwent apical prolapse surgery between January 1, 2011, and July 31, 2017. Only symptomatic uterine or vaginal vault prolapse patients with stage 2-4, according to the pelvic organ prolapse quantification system, were included. Baseline and intraoperative variables of groups; perioperative complications, including hemorrhage, urinary, and wound complications, blood transfusion, ileus, and short-term outcomes were compared. Results: A total of 68 abdominal sacrocolpopexies (44 sacrocolpopexies and 24 sacrohysteropexies), 14 laparoscopic sacrocolpopexies (10 sacrocolpopexies and 4 sacrohysteropexies), and 28 laparoscopic pectopexies (16 pectopexies and 12 pectohysteropexies) were analyzed. Baseline characteristics and intraoperative variables were similar. However, the mean operating time was significantly shorter in the laparoscopic pectopexy group (74.9 min) when compared with that of the other groups (p < 0.01). During the six-month follow-up period, no prolapse recurrence and mesh erosion / exposure were observed in any group. De-novo stress urinary incontinence, urgency, and defecation problems, as well as perioperative complication rates, were not statistically significantly different between the groups. Conclusions: Although the complication rates and short-term outcomes were not significantly different between the groups, minimally invasive approaches were associated with reduced procedural-related morbidity. Laparoscopic pectopexy is a promising endoscopic prolapse surgery and can be an alternative technique to sacrocolpopexy.